RTID-03. DSP-0390, AN ORAL EMOPAMIL BINDING PROTEIN (EBP) INHIBITOR, IN PATIENTS WITH RECURRENT HIGH-GRADE GLIOMA: A FIRST-IN-HUMAN, PHASE 1 STUDY. (14th November 2022) - Reardon, David A; Narita, Yoshitaka; Arakawa, Yoshiki; Goldlust, Samuel; Anstass, George; McMullen, Dragana; Dow, Edward; Seki, Masataka; Furuta, Yudai; Song, Gregory; Colman, Howard
Abstract: The brain's cells are dependent on their own biosynthesis of cholesterol as the blood-brain barrier prevents uptake from the circulation. In normal glial cells, regulation of cholesterol synthesis depends on cell density and is turned off when density exceeds a certain level. Gliomas maintain high levels of cholesterol synthesis genes to support abnormal growth. Upregulation of cholesterol synthesis genes is associated with decreased survival in patients with glioblastoma (GBM). Therefore, gliomas are potentially sensitive to cholesterol synthesis inhibition. DSP-0390, an investigational small molecule, inhibits EBP, an enzyme in one of the last, crucial steps of cholesterol biosynthesis. By inhibiting cholesterol synthesis, cytotoxicity can be induced selectively against hyperproliferative GBM cells. DSP-0390 has shown significant antitumor activity in orthotopic xenograft models of human GBM (data on file).DSP-0390 will be evaluated in a phase 1 study in patients with recurrent, high-grade glioma (NCT05023551). Key eligibility criteria: age >18 years; Karnofsky Performance Status score >70%; adequate renal, hepatic, and hematologic function. Patients must not have multifocal disease, leptomeningeal metastasis or extracranial metastasis, abnormal electrocardiograms, or significant cardiovascular disease. In Dose Escalation, 21-30 patients with World Health Organization (WHO) grade III or IV malignant glioma who progressed after >1 prior therapy will be enrolled. Dose level enrollment will be guided by a Bayesian Logistic Regression Model until identification of the maximum tolerated dose or recommended dose for expansion. Dose Expansion for clinical activity will enroll approximately 20-40 patients with WHO grade IV GBM who progressed after primary therapy and have measurable disease. Patients will receive oral DSP-0390 once daily. Study endpoints include safety (treatment-emergent adverse events [AEs], serious AEs, and dose-limiting toxicities), efficacy (6-month progression-free survival [PFS], objective response, PFS, duration of response, and 12-month overall survival), pharmacokinetics (PK), and pharmacodynamic biomarkers. This study is currently recruiting in the United States and Japan.